(untitled) (World Bulletin of Management and Law, 2023)
This article covers some of the problems in the qualification of crimes against Justice by the author, these problems were systematically analyzed and concluded on the basis of the norms of Criminal Law of foreign countries, and proposals and recommendations were developed within the framework of the topic.